India is broken a people betrayed, Independence to today - Mody, Ashoka (California Stanford University Press, 2023)
When Indian leaders first took control of their government in 1947, they proclaimed the ideals of national unity and secular democracy. Through the first half century of nation-building, leaders could point to uneven but measurable progress on key goals, and after the mid-1980s, dire poverty declined for a few decades, inspiring declarations of victory. But today, a vast majority of Indians live in a state of underemployment, and are one crisis away from despair. Public goods--health, education, cities, air and water, and the judiciary--are in woeful condition. And good jobs will remain scarce as long as that is the case. The lack of jobs will further undermine democracy, which will further undermine job creation. India is Broken provides the most persuasive account available of this economic catch-22. Challenging prevailing narratives, Mody contends that successive post-independence leaders, starting with its first Prime Minister, Jawaharlal Nehru, failed to confront India's true economic problems, seeking easy solutions instead. As a popular frustration grew, and corruption in politics became pervasive, India's economic growth relied increasingly on unregulated finance, and environmentally destructive construction. The rise of a violent Hindutva has buried all prior norms in civic life and public accountability. Combining statistical data with creative media, such as literature and cinema, to create strong, accessible, people-driven narratives, this book is a meditation on the interplay between democracy and economic progress, with lessons extending far beyond India. Mody proposes a path forward that is fraught with its own peril, but which nevertheless offers something resembling hope"
Includes bibliographical references (pages 413-490) and index.
Keywords: India--Economic conditions--1947-